Hubungan Intensitas Mengakses E-Commerce dengan Perilaku Belanja Impulsif Secara Daring Pada Dewasa Awal di Jakarta - Edith, Faustina (Psikologi UHAMKA, 2023)
Technology development had given a significant impact on the development of e-commerce. The offerings available on e-commerce make the user have the tendency to be impulsive with their purchase. The hypothesis of this study is there’s a relationship between frequently accessing e-commerce and impulsive buying behavior among early aged-adults. The participants in this research are early adults aged 18 to 25 years old and live in DKI Jakarta, with a total of participants being 88 women and 31 men. The sampling technique in this research is convenience sampling. A quantitative study was designed for this research and used a correlational method to analyze the data. The measurement tool in this research is the impulsive buying scale developed by Rook & Fisher (1995) with a total item correlation is 0.37 to 0.70 and Cronbach alpha around 0.834, whereas measurement of intensity access e-commerce is measured using classification on 3 categories which are the intensity of access e-commerce 1-5 times, 6-10 times, and more than 10 times per month. The data collection method used an online questionnaire. The normality test was used as an assumption test and the correlation product moment was used to analyze the data. This study’s results showed that there is a low correlation between frequently accessing e-commerce and impulsive buying behavior (r = 0.205; p = 0.025). Also, the research showed that 70.5% of the participant were categorized as high on the impulsive buying scale. This study implies that individual’s online activity may influence their behavior in purchasing.